Walc panny Ludwiki / Hanna Januszewska; illustrowal Wieslaw Majchrzak. - Januszewska, Hanna; Majchrak, Wieslaw (Warszawa : Nasza Ksiegarnia, 1988)
A collection of poems for young children. Ages 8-12.
Keywords: Polish poetry -- 20th century -- Juvenile literature